The Department Chair and Creative Leadership - Julia Hovanec (Academic Chairpersons Conference Proceedings, 2023)
Leading a department in the ever-changing and, at times, tumultuous landscape of higher education calls for creative problem-solving and divergent thinking. Participants will engage in specific creative leadership strategies using creativity as a reflective practice and as a means to lead boldly. The goals are to spur change while cultivating an inclusive department.
Keywords: Creative Leadership; Divergent Thinking; Creative Problem-solving